St. Louis Diagnostic and Detoxification Center: An Experiment in Non-Criminal Processing of Public Intoxicants - Raymond T. Nimmer (Washington University Law Quarterly, 1970)
This Article discusses the results of an American Bar Foundation study of the oldest and the most widely publicized detoxification program, the St. Louis Detoxification and Diagnostic Center for Intoxicated Men. The results of this study are significant on two levels. First, and most obvious, the study provides a means to evaluate the impact of the St. Louis program. Second, the problems and achievements of the St. Louis program provide a base from which to speculate concerning the concept of replacing criminal laws with civil detoxification systems.
Keywords: Intoxication; Drunkenness; Skid Row